2016
DOI: 10.1037/adb0000188
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking and ADHD: An examination of prognostically relevant smoking behaviors among adolescents and young adults.

Abstract: Introduction Attention deficit/hyperactivity disorder (ADHD) is associated with health risks in adolescence which includes the potential for smoking cigarettes, early smoking initiation, and rapid progression to daily smoking. Much less is known, however, about prognostically-relevant smoking behaviors among individuals with childhood ADHD. Further research in this area is important for identifying individuals at pronounced risk for nicotine addiction, and for developing effective interventions for this popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
44
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 128 publications
11
44
3
Order By: Relevance
“…Our findings confirm the most consistently reported SU risk associated with ADHD – cigarette smoking – 36% of ADHD vs. 18% of LNCG. Similar large group differences were reported in smaller and/or single‐site studies (Barkley et al., ; Klein et al., ; Lambert & Hartsough, ; Rhodes et al., ). Given the well‐established negative health consequences of cigarette smoking (e.g., Lubin & Caporaso, ), and that cessation is especially difficult for those with ADHD (Humfleet et al., ; Mitchell, Weisner et al., ), the need for improved smoking prevention in ADHD is substantial.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Our findings confirm the most consistently reported SU risk associated with ADHD – cigarette smoking – 36% of ADHD vs. 18% of LNCG. Similar large group differences were reported in smaller and/or single‐site studies (Barkley et al., ; Klein et al., ; Lambert & Hartsough, ; Rhodes et al., ). Given the well‐established negative health consequences of cigarette smoking (e.g., Lubin & Caporaso, ), and that cessation is especially difficult for those with ADHD (Humfleet et al., ; Mitchell, Weisner et al., ), the need for improved smoking prevention in ADHD is substantial.…”
Section: Discussionsupporting
confidence: 77%
“…Early, frequent, or heavy adolescent SU poses a well‐known risk for later SU disorder (Chassin, Pitts, & Prost, ; Chen, Storr, & Anthony, ; Nelson, van Ryzin, & Dishion, ). Several longitudinal studies inconsistently report about early initial use for various substances among adolescents with ADHD (Groenman et al., ; Molina & Pelham, ; Molina, Pelham, Gnagy, Thompson, & Marshal, ; Rhodes et al., ; Sibley et al., ). A few of these studies reported atypically frequent and/or heavy use (Burke, Loeber, & Lahey, ; Molina & Pelham, ; Molina et al., , ; Sibley et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…We were able to replicate previously reported associations between genetic liability for ADHD and lower educational attainment (12, 13), higher prevalence of smoking (14), younger age at delivery (15) and higher body mass index (16). While the previous findings for smoking and BMI were identified in young adults, our findings using an adult population-based sample with a mean age of 56 years, suggest that associations of childhood psychiatric disorder genetic liabilities with health and social outcomes persist into later adulthood.…”
Section: Discussionsupporting
confidence: 75%
“…Further, other aspects, for example, the type of criminal offenses and overdose-related incidents, were included in the analysis. The variables were chosen according to previous work in this field, which showed that they might be associated with symptoms of ADHD: imprisonment [11,32], nicotine consumption [33,34], employment [35,36], gender [37,38], type of committed crimes [39], and hospital admissions [40]. High-risk drug use (e.g., Intravenous drug use, overdose-related incidences) was chosen as it has been shown to be associated with impulsivity [41][42][43].…”
Section: Introductionmentioning
confidence: 99%